Reason, religion, and the Australian polity - Chavura, Stephen A., author.
1 online resource.
Keywords: "How did the concept of the secular state emerge and evolve in Australia and how has it impacted on its institutions? This is the most comprehensive study to date on the relationship between religion and the state in Australian history, focusing on the meaning of political secularity in a society that was from the beginning marked by a high degree of religious plurality. This book tracks the rise and fall of the established Church of England, the transition to plural establishments, the struggle for a public Christian-secular education system, and the eventual separation of church and state throughout the colonies. The study is unique in that it does not restrict its concern with religion to the churches but also examines how religious concepts and ideals infused apparently secular political and social thought and movements making the case that much Australian thought and institution building has had a sacral-secular quality. Social welfare reform, nationalism, and emerging conceptions of citizenship and civilization were heavily influenced by religious ideals, rendering problematic traditional linear narratives of secularisation as the decline of religion. Finally the book considers present day pluralist Australia and new understandings of state secularity in light of massive social changes over recent generations"--